Sustentabilidade na Baía de Suape: entre o Complexo Industrial Portuário de Suape e a Festa da Ouriçada - Santos, Juana de Oliveira (2013)
This thesis called Sustainability in Suape Bay: between the Suape Port and Industrial Complex and the Sea Urchin Festival seek to understand the relationship into the realization of the Sea Urchin Festival as a cultural and folk religious manifestation of Suape region. The relationships maintained by the population that inhabits the Suape Bay for generations is a complexity composed by relevant elements as historical, economic, social, cultural or environmental which are analyzed in this study. Through a quantitative and qualitative perspective, we seek to analyze the mode of production and reproduction of theirs lives, which are strongly attached with elements of the local nature, as well the marine territory category and with their cultural manifestations. They are facing the growing social changes resulted by the pressures coming from the enterprises and the development promises of the most emblematic economic policy megaproject of Pernambuco State, the Suape Port and Industrial Complex. We can say that the contemporary scenario showed to the Suape population, who are rooted into a rustic culture and traditional modal of life based on their small scale fishing practice, is a turning point, once some of them realize they are living one social and environmental conflict against the economic development machine, in the same time that others see each other in an uprooting process with their own territory. So there are some of the Sea Urchin Festival expressions that now just belong to the social and folk memory sphere, as well other ones get the drift, getting an uncertain way.